Polyolefin composition obtained from recycled polyolefin

By introducing recycled polyethylene (r-PE) and other specific components into the polypropylene composition, the problem of difficulty and poor separation in polyolefin recycling is solved, and a high-performance and sustainable polypropylene composition is achieved, suitable for high-performance applications.

CN119731260AInactive Publication Date: 2025-03-28BASELL POLIOLEFINE ITALIA SRL
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380060555.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-14
Filing Date
2023-08-21
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In polyolefin recycling, it is difficult to quantitatively separate polypropylene (PP) and polyethylene (PE), resulting in the deterioration of mechanical and optical properties and poor compatibility during the remodeling process, affecting the reliability and performance of the product.

Method used

Using a polypropylene composition, which includes crystalline propylene polymers, elastomeric copolymers of ethylene and propylene, recycled polyethylene (r-PE) and crystalline propylene homopolymers, improves the performance and sustainability of the composition by specific component ratios and processing methods.

Benefits of technology

The polypropylene composition maintains high performance while improving the reliability and sustainability of recycled materials and is suitable for high performance applications, especially in water management systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005275965760000071
    Figure BDA0005275965760000071
  • Figure BDA0005275965760000081
    Figure BDA0005275965760000081
  • Figure BDA0005275965760000082
    Figure BDA0005275965760000082
Patent Text Reader

Abstract

A polypropylene composition comprising: (a) from 45.7% to 69.7% by weight of a crystalline propylene polymer; (b) from 5.3% to 29.3% by weight of an elastomeric copolymer of ethylene and propylene; (c) from 3.0% to 27.0% by weight of recycled polyethylene (r-PE); d) from 1.0% to 15.0% by weight of a crystalline propylene homopolymer; the percentages of (a), (b), (c) and (d) are relative to the sum of (a), (b), (c) and (d).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to polyolefin compositions containing recycled polyethylene that are useful for injection molded articles, particularly for grates and pails. Background Art

[0002] In WO 2006 / 125720 a polyolefin composition for this use is described, the polyolefin composition being made of: a) 65% to 77%, preferably 70% to 77%, of a crystalline propylene polymer having an amount of isotactic pentads (mmmm) higher than 97.5 mol % measured by 13C-MNR on the fraction insoluble in xylene at 25° C. and a polydispersity index ranging from 5 to 10; b) 8% to less than 13%, preferably 9% to 12%, of an elastomer of ethylene and propylene A copolymer having an amount of repeating units derived from ethylene in the range from 30% to 70%, preferably from 35% to 60%, and being partially soluble in xylene at ambient temperature; the polymer fraction soluble in xylene at ambient temperature having an intrinsic viscosity value in the range from 2 dl / g to 4 dl / g; and c) 10% to 23%, preferably 10% to 20%, of polyethylene having an intrinsic viscosity value in the range from 1.5 dl / g to 4 dl / g, and optionally containing repeating units derived from propylene in an amount lower than 10%.

[0003] Polyolefin compositions suitable for these applications have good stiffness, impact resistance and stress whitening resistance.

[0004] In general, polyolefin compositions, although appreciated in terms of performance, raise concerns in terms of sustainability, particularly with reference to the fact that their production is based on the use of non-renewable resources.

[0005] Therefore, a common attempt to alleviate this problem is to use variable amounts of recycled polyolefins, such as polypropylene or polyethylene, in the multicomponent polyolefin composition.

[0006] Recycled polyolefins are derived from post-consumer waste (PCW) material streams that are separated from other polymers (such as PVC, PET or PS) through various steps.

[0007] In polyolefin recycling, especially when processing material streams from post-consumer waste (PCW), one of the key issues is the difficulty in quantitatively separating polypropylene (PP) from polyethylene (PE), and vice versa. Therefore, despite being referred to as recycled PE (rPE) or recycled PP (rPP), commercial products from PCW sources have been found to be a mixture of various amounts of PP and PE.

[0008] This fact, coupled with the presence in the recycled materials of additives and secondary components that may not be fully adapted to the application in which they are supposed to be used, leads to such recycled PP / PE blends suffering from deterioration of mechanical and optical properties during remodeling and poor compatibility between the main polymer phases. As a result, the reliability of articles using r-PP or r-PE is considered lower, due to the lower performance of the compositions used in these articles.

[0009] Therefore, the use of recycled materials in applications requiring high performance levels is strongly discouraged and limited to low-cost and less demanding applications.

[0010] It has now been unexpectedly found that the presence of recycled PE components in certain polypropylene compositions for use in water management systems does not impair performance and makes their production processes more sustainable. Summary of the invention

[0011] Therefore, the object of the present disclosure is a polypropylene composition comprising:

[0012] (a) from 45.7 to 69.7 wt%, preferably from 47.7 to 67.7 wt%, more preferably from 50.7 to 64.7 wt% of a crystalline propylene polymer having 13 C-MNR measured on the fraction insoluble in xylene at 25° C., an amount of isotactic pentads (mmmm) higher than 97.0 mol % and a polydispersity index ranging from 3 to 15;

[0013] (b) from 5.3 to 29.3 wt. %, preferably from 7.3 to 27.3 wt. %, more preferably from 10.3 to 24.3 wt. % of an elastomeric copolymer of ethylene and propylene having 13 repeating units derived from ethylene in an amount ranging from 30.0 wt% to 70.0 wt%, preferably from 35.0 wt% to 60.0 wt%, more preferably from 40.0 wt% to 53.0 wt% as measured by C-MNR;

[0014] Wherein in the blend of components a) and b):

[0015] i) the xylene-soluble polymer fraction of component a) + b) at 25° C. ranges from 10.0 wt % to 32.5 wt %; preferably ranges from 14.0 wt % to 28.2 wt %; more preferably ranges from 17.0 wt % to 25.1 wt %;

[0016] ii) the xylene-soluble polymer fraction of components a) + b) at 25°C has an intrinsic viscosity value measured in tetralin at 135°C in the range from 1.5 dl / g to 2.8 dl / g; preferably in the range from 1.7 dl / g to 2.7 dl / g; more preferably in the range from 1.8 dl / g to 2.6 dl / g;

[0017] iii) By 13 The content of ethylene-derived units in the fraction soluble in xylene at 25° C. of component a) + b as measured by C-MNR is in the range of from 24.4% to 43.5% by weight; preferably in the range of from 29.0% to 40.0% by weight; more preferably in the range of from 32.0% to 39.0% by weight;

[0018] iv) the melting point of component a) + b as measured by DSC ranges from 148.0°C to 168.0°C; preferably ranges from 154.0°C to 167.0°C; more preferably ranges from 162.0°C to 166.0°C;

[0019] v) the melt flow rate (ISO 1133-1230°C / 2.16kg) of component a) + b ranges from 10.0 g / 10min to 30.0 g / 10min; preferably ranges from 13.0 g / 10min to 25.0 g / 10min; more preferably ranges from 16.0 g / 10min to 22.0 g / 10min;

[0020] The polypropylene composition further comprises:

[0021] (c) from 3.0 wt% to 27.0 wt%, preferably from 5.0 wt% to 25.0 wt%, more preferably from 7.0 wt% to 23.0 wt% of recycled polyethylene (r-PE) having a melt flow rate (ISO 1133-1190°C / 2.16 Kg) from 0.1 g / 10 min to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component,

[0022] d) from 1.0 to 15.0 wt%, preferably from 5.0 to 13.0 wt%, more preferably from 7.0 to 12.0 wt% of a crystalline propylene homopolymer having a melt flow rate (ISO 1133-1230°C / 2.16 kg) in the range from 0.3 to 10.0 g / 10 min; preferably in the range from 1.0 to 5.0 g / 10 min, more preferably in the range from 1.5 to 3.0 g / 10 min and in the range from 0.850 to 0.850 g / cm 3 Up to 0.950g / cm3 ; preferably from 0.870g / cm 3 Up to 0.930g / cm 3 More preferably from 0.890g / cm 3 Up to 0.910g / cm 3 Density (ISO 1183-1);

[0023] The entire composition has a melt flow rate (ISO 1133-1230°C / 2.16kg) value ranging from 3.0 g / 10min to 21.0 g / 10min; preferably from 4.3 g / 10min to 18.0 g / 10min; more preferably from 9.0 g / 10min to 16.0 g / 10min;

[0024] The percentages of (a), (b), (c) and (d) are relative to the sum of (a), (b), (c) and (d). DETAILED DESCRIPTION

[0025] The term "copolymer" as used herein refers to polymers having two different repeating units in the chain and polymers having more than two different repeating units, such as terpolymers. "Ambient temperature" herein means a temperature of 25°C (room temperature).

[0026] The term "crystalline propylene polymer" means in the present application a propylene polymer having an amount of isotactic pentads (mmmm) higher than 70 mol%, the amount of isotactic pentads (mmmm) being measured by 13C-MNR on the fraction insoluble in xylene at 25°C; an "elastomeric" polymer is understood to mean a polymer having a solubility in xylene at ambient temperature higher than 50 wt%.

[0027] Not all characteristics of copolymers (a) to (d) are inextricably linked to one another. This means that a certain level of preference for one of these characteristics does not necessarily involve the same level of preference for the remaining characteristics.

[0028] The crystalline propylene polymer (a) is selected from propylene homopolymers and propylene copolymers containing up to 3.0 wt.% of ethylene or C4-C10 α-olefins or a combination thereof. Particularly preferred are propylene homopolymers.

[0029] Preferably, the polydispersity index ranges from 3 to 10.

[0030] The r-PE (c) is a crystalline or semi-crystalline high density PE (r-HDPE) selected from commercial PCW (e.g. post-consumer waste from municipalities). Preferably, the r-PE (c) has a molecular weight ranging from 0.940 g / cm 3 Up to 0.965g / cm 3The density (ISO 1183-1) and the melt flow rate (ISO 1133-1190°C / 2.16Kg ISO 1133-1) of from 0.1 g / 10 min to 1.0 g / 10 min.

[0031] Prior to its use, the plastic mixture containing rHDPE undergoes a standard recycling process, including collection, shredding, sorting and washing. Although the sorted rHDPE is composed of a large amount of HDPE, it always contains small amounts of other polymers and / or inorganic components. In particular, the r-PE according to the present disclosure contains a polypropylene content in an amount of from 1.0 wt % to 15 wt %, preferably from 5 wt % to a maximum of 10 wt % of the total r-PE component.

[0032] In a preferred embodiment, the r-PE comprises a crystalline polyethylene fraction, wherein the amount of repeating units derived from propylene in the polyethylene chain is less than 11 wt%, and most preferably they are absent, i.e. most preferably the r-PE is an ethylene homopolymer containing the above inclusions. Preferably, (r-PE) has a melt flow rate (ISO 1133-1190°C / 2.16Kg ISO 1133-1) of from 0.1 g / 10min to 1.0 g / 10min, and more preferably from 0.1 g / 10min to 0.5 g / 10min.

[0033] r-PE is commercially available. An example of a suitable r-PE grade is represented by the ivory or grey version of the grade sold by Lyondellbasell under the trade name Hostalen QCP5603.

[0034] The compositions of the present disclosure preferably show tensile modulus values ​​of at least 1000 MPa, preferably from 1050 MPa to 1700 MPa, even more preferably from 1100 MPa to 1600 MPa.

[0035] The Charpy impact resistance value at 23°C is preferably higher than 10.0 kJ / m 2 , preferably in the range of 10.5 kJ / m 2 Up to 18.0kJ / m 2 , more preferably in the range of 11.0 kJ / m 2 Up to 17.0 kJ / m 2 ; The Charpy impact resistance at 0°C is preferably greater than 6.0 kJ / m 2 , preferably in the range of 6.5 kJ / m 2 Up to 12.0 kJ / m 2 , more preferably in the range of 7.0 kJ / m 2 Up to 10.0kJ / m 2 , and the Charpy impact resistance at -20°C is preferably at least 4.0 kJ / m2 ; The preferred range is from 4.5kJ / m 2 Up to 10.0kJ / m 2 .

[0036] Component d) is a propylene homopolymer obtainable according to procedures known in the art. In particular, component d) may be a commercial product such as Adstif HA622H sold by Lyondellbasell.

[0037] The composition of the present disclosure can be obtained by mechanically blending components (a) to (d) according to conventional techniques.

[0038] According to a preferred method of preparation, components (c) and (d) are mechanically blended with a preformed multiphase composition comprising components (a) and (b) associated together by a sequential copolymerization process.

[0039] The process comprises polymerizing propylene alone or in a mixture with a small amount of ethylene in a first stage and then polymerizing propylene with a higher amount of ethylene in a second stage, both stages being carried out in the presence of a catalyst comprising the reaction product between:

[0040] i) a solid catalyst component comprising Ti, Mg, Cl and at least one internal electron body compound;

[0041] ii) an alkylaluminum compound and,

[0042] iii) external electron donor compounds having the following general formula:

[0043] (R 7 ) a (R 8 ) b Si(OR 9 ) c , wherein a and b are integers from 0 to 2, c is an integer from 1 to 4, and the sum of (a+b+c) is 4; R 7 , R 8 and R 9 is an alkyl, cycloalkyl or aryl radical having 1 to 18 carbon atoms which may optionally contain heteroatoms.

[0044] The internal donor is preferably selected from esters of mono- or dicarboxylic organic acids, such as benzoates, malonates, phthalates and certain succinates. Examples of internal donors are described in US 4522930A, EP 045977A2 and international patent applications WO 00 / 63261 and WO 01 / 57099. Particularly suitable are phthalates and succinates. Alkyl phthalates are preferred, such as diisobutyl phthalate, dioctyl phthalate and diphenyl phthalate and benzyl butyl phthalate.

[0045] The particles of solid component (i) may have a substantially spherical morphology and an average diameter ranging between 5 μm and 150 μm, preferably from 20 μm to 100 μm, and more preferably from 30 μm to 90 μm. As particles having a substantially spherical morphology, those particles are meant in which the ratio between the larger axis and the smaller axis is equal to or lower than 1.5, and preferably lower than 1.3.

[0046] The amount of Mg may preferably range from 8 to 30%, more preferably from 10 to 25 wt%.

[0047] The amount of Ti may range from 0.5 wt % to 7 wt %, and more preferably from 0.7 wt % to 5 wt %.

[0048] According to one method, the solid catalyst component (i) can be prepared by reacting a titanium compound of the formula Ti(OR)q-yXy (where q is the valence of titanium and y is a number between 1 and q, preferably TiCl4) with magnesium chloride derived from an adduct of the formula MgCl2·pROH (where p is a number between 0.1 and 6, preferably from 2 to 3.5, and R is a hydrocarbon radical having 1 to 18 carbon atoms). The adduct can be suitably prepared in spherical form by mixing an alcohol and magnesium chloride, operating under stirring conditions at the melting temperature of the adduct (100°C to 130°C). The adduct is then mixed with an inert hydrocarbon immiscible with the adduct, thereby producing an emulsion, which is rapidly quenched, causing the adduct to solidify in the form of spherical particles. Examples of spherical adducts prepared according to this procedure are described in USP 4,399,054 and USP4,469,648. The adduct thus obtained can be reacted directly with the Ti compound, or it can be previously subjected to a thermally controlled dealcoholation (80° C. to 130° C.) to obtain an adduct in which the number of moles of alcohol is lower than 3, preferably between 0.1 and 2.5. The reaction with the Ti compound can be carried out by suspending the adduct (dealcoholated or as such) in cold TiCl4; the mixture is heated to 80° C. to 130° C. and maintained at this temperature for 0.5 to 2 hours. The treatment with TiCl4 can be carried out once or more. The electron donor compound can be added during the treatment with TiCl4 in the desired ratio.

[0049] The alkyl-Al compound (ii) is preferably selected from trialkylaluminum compounds, such as, for example, triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum. It is also possible to use alkylaluminum halides, alkylaluminum hydrides or alkylaluminum sesquichlorides, such as AlEt2Cl and Al2Et3Cl3, possibly mixed with the above trialkylaluminums. The Al / Ti ratio is higher than 1 and may preferably be in the range between 50 and 2000.

[0050] Particularly preferred are silicon compounds (iii) in which a is 1, b is 1, c is 2, at least one of R7 and R8 is selected from a branched alkyl, cycloalkyl or aryl group having 3 to 10 carbon atoms, optionally containing heteroatoms, and R9 is a C1-C10 alkyl group, in particular a methyl group. Examples of such preferred silicon compounds are methylcyclohexyldimethoxysilane (C donor), diphenyldimethoxysilane, methyl tert-butyldimethoxysilane, dicyclopentyldimethoxysilane (D donor), diisopropyldimethoxysilane, (2-ethylpiperidinyl)tert-butyldimethoxysilane, (2-ethylpiperidinyl)tert-hexyldimethoxysilane, (3,3,3-trifluoro-n-propyl) (2-ethylpiperidinyl) dimethoxysilane, methyl (3,3,3-trifluoro-n-propyl) dimethoxysilane. In addition, also preferred are silicon compounds wherein a is 0, c is 3, R8 is a branched alkyl or cycloalkyl group optionally containing heteroatoms, and R9 is a methyl group. Examples of such preferred silicon compounds are cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane and tert-hexyltrimethoxysilane.

[0051] The external electron donor compound (iii) is used in such an amount that the molar ratio between the organoaluminium compound and said external electron donor compound (iii) is from 0.1 to 200, preferably from 1 to 100 and more preferably from 3 to 50.

[0052] The polymerization process can be carried out in the gas phase, operating in one or more fluidized bed or mechanically stirred bed reactors, using an inert hydrocarbon solvent as diluent for slurry polymerization, or using a liquid monomer (such as propylene) as the reaction medium for bulk polymerization.

[0053] Preferably, the multiphase composition used in the present disclosure is obtained by a sequential polymerization process in two or more stages, wherein component (a) is obtained in a first stage and then component (b) is obtained in the presence of component (a) in a second stage. Each stage can be carried out in the gas phase, operating in one or more fluidized bed or mechanically stirred bed reactors, or bulk polymerization using liquid monomer (e.g. propylene) as the reaction medium. Also preferred is a hybrid process, wherein one stage (preferably the stage for preparing component (a)) is carried out in liquid monomer and another stage (preferably the stage for preparing component (b)) is carried out in the gas phase.

[0054] According to a preferred embodiment, component (a) is prepared in a gas phase reactor, as described in EP 782587, comprising a first and a second interconnected polymerization zone, into which propylene and optionally ethylene are fed in the presence of a catalyst system and from which the produced polymer is discharged. The growing polymer particles flow under fast fluidization conditions through the first said polymerization zone (riser), leave the first polymerization zone and enter the second said polymerization zone (downcomer), where they flow under gravity in a densified form through the second polymerization zone, leave the second polymerization zone and are reintroduced into the first polymerization zone, thereby establishing a polymer circulation between the two polymerization zones. Typically, fast fluidization conditions in the first polymerization zone are established by feeding a monomer gas mixture below the point at which the growing polymer is reintroduced into the first polymerization zone. The velocity of the transport gas into the first polymerization zone is higher than the transport velocity under operating conditions and is typically between 2 m / s and 15 m / s. In the second polymerization zone, in which the polymer flows in a densified form under the action of gravity, a high solid density value close to the bulk density of the polymer is reached; therefore, a positive pressure gain can be obtained along the flow direction, so that the polymer can be reintroduced into the first reaction zone without the help of mechanical means. In this way, a "loop" circulation is established, which is defined by the pressure balance between the two polymerization zones and the head loss introduced into the system. Optionally, one or more inert gases, such as nitrogen or aliphatic hydrocarbons, are maintained in the polymerization zone in an amount such that the sum of the partial pressures of the inert gases is preferably between 5% and 80% of the total gas pressure. Preferably, the various catalyst components are fed to the first polymerization zone at any point in the first polymerization zone. However, they can also be fed at any point in the second polymerization zone. Molecular weight regulators known in the art (particularly hydrogen) can be used to adjust the molecular weight of the growing polymer. If a bimodal setting is required, a barrier flow that separates the polymerization environments of the riser and the downcomer as described in EP-A-1012195 can be used.

[0055] The polymerization can be carried out at a temperature of from 20°C to 120°C, preferably from 40°C to 80°C. When the polymerization is carried out in the gas phase, the operating pressure can range between 0.5 MPa and 5 MPa, preferably between 1 MPa and 4 MPa. In bulk polymerization, the operating pressure can range between 1 MPa and 8 MPa, preferably between 1.5 MPa and 5 MPa. Hydrogen can be used as a molecular weight regulator.

[0056] If desired, the final multiphase composition comprising (a) + (b) can be chemically treated with an organic peroxide to reduce the average molecular weight and increase the melt flow index to the value required for a particular application.

[0057] The final composition comprising components (a) to (d) can be added with conventional additives, fillers and pigments commonly used in olefin polymers, such as nucleating agents, extender oils, mineral fillers and other organic and inorganic pigments. In particular, the addition of inorganic fillers, such as talc, calcium carbonate and mineral fillers, will also improve some mechanical properties, such as flexural modulus and HDT. Talc can also have a nucleating effect.

[0058] For example, the nucleating agent is added to the composition of the present disclosure in an amount ranging from 0.05 wt % to 2 wt %, more preferably from 0.1 wt % to 1 wt %, relative to the total weight.

[0059] The polypropylene composition object disclosed herein can be used to obtain injection molded articles of various objects. Particularly preferred is the use of the polypropylene composition for preparing an automotive battery box.

[0060] As shown in the examples below, compositions employing r-PE do not show any degradation in properties relative to compositions employing virgin PE having similar characteristics.

[0061] The following examples are given to illustrate but not to limit the present disclosure.

[0062] Examples

[0063] Characterization

[0064] Xylene soluble (XS) fraction at 25°C

[0065] 2.5g of polymer and 250ml of xylene were introduced into a glass flask equipped with a refrigerator and a magnetic stirrer. The temperature was raised to the boiling point of the solvent within 30 minutes. The resulting clear solution was then kept under reflux and stirred for 30 minutes. The closed flask was then kept in an ice water bath for 30 minutes and then in a 25°C constant temperature water bath for 30 minutes. The resulting solid was filtered on a quick filter paper. 100ml of the filtrate was poured into a pre-weighed aluminum container, which was heated on a heating plate under a nitrogen stream to remove the solvent by evaporation. The container was then kept in an oven at 80°C under vacuum until constant weight was reached. The weight percentage of the polymer soluble in xylene at room temperature was then calculated.

[0066] The content of the xylene soluble fraction is expressed as a percentage of the original 2.5 g and then expressed as a xylene insoluble percentage (%) by difference (made up to 100%);

[0067] Melt flow rate (MFR)

[0068] Unless otherwise specified, measured according to ISO 1133-1 at 230°C and a load of 2.16 kg.

[0069] density

[0070] Measured according to ISO 1183-1.

[0071] Intrinsic viscosity (IV)

[0072] The sample is dissolved in tetralin at 135°C and then poured into a capillary viscometer. The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass jacket; this setup allows temperature control with a circulating thermostatic liquid. The downward passage of the meniscus is timed by a photoelectric device.

[0073] The passage of the meniscus in front of the upper lamp starts a counter with a quartz crystal oscillator. When passing the lower lamp, the meniscus stops the counter and the outflow time is recorded: this is converted into an intrinsic viscosity value by Huggins' equation (Huggins, ML, J. Am. Chem. Soc., 1942, 64, 2716), provided that the flow time of the pure solvent under the same experimental conditions (same viscometer and same temperature) is known. A single polymer solution is used to determine [η].

[0074] Polydispersity index: measured by using a parallel plate rheometer model RMS-800 sold by RHEOMETRICS (USA) at a temperature of 200°C, operating at an oscillation frequency increasing from 0.1 rad / s to 100 rad / s. From the crossover modulus, the PI can be derived by the following equation:

[0075] PI=105 / Gc

[0076] Where Gc is the crossover modulus, which is defined as the value (expressed in Pa) where G'=G", where G' is the storage modulus and G" is the loss modulus.

[0077] Ethylene (C2) content

[0078] Propylene / ethylene copolymer 13 C NMR

[0079] 13C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe, operating at 120°C in Fourier transform mode at 160.91 MHz.

[0080] The peak of the Sββ carbon at 29.9 ppm (according to the nomenclature of "Monomer sequence distribution in ethylene-propylene rubber measured by 13C NMR. 3. Use of reaction probability models" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, 10, 536) was used as an internal reference. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at a concentration of 8 weight / volume % at 120°C. Each spectrum was acquired with 90° pulses with a 15 second delay between pulses, and CPD was used to remove 1H-13C coupling. 512 transient data were stored in 32K data points using a spectral window of 9000 Hz.

[0081] Evaluation of spectral assignments, triplet distribution, and composition was performed according to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride" M. Kakugo, Y. Naito, K. Mizunuma, and T. Miyatake, Macromolecules, 1982, 15, 1150) using the following equation:

[0082] PPP=100T ββ / S PPE=100T βδ / S EPE=100T δδ / S

[0083] PEP=100s ββ / S PEE=100S βδ / S EEE=100(0.25S γδ +0.5S δδ ) / S

[0084] S=T ββ +T βδ +T δδ +S ββ +S βδ +0.25S γδ +0.5S δδ

[0085] The mole percent ethylene content was estimated using the following equation:

[0086] E%mol=100*[PEP+PEE+EEE]. The weight percentage of ethylene content was estimated using the following equation:

[0087]

[0088] Where P mol% is the molar percentage of propylene content, and MW E and MW P are the molecular weights of ethylene and propylene respectively.

[0089] The product of the reaction ratios r1r2 is calculated as follows according to Carman (CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977; 10, 536):

[0090]

[0091] The stereoregularity of the propylene sequence was calculated as the mm content from the ratio of PPP mmTββ (28.90 ppm to 29.65 ppm) and total Tββ (29.80 ppm to 28.37 ppm).

[0092] The ethylene C2 content of component b2 has been measured by measuring the C2 content on component B) and then calculated by using the formula C2tot=Xb1C2b1+Xb2C2b2, where Xb1 and Xb2 are the amounts of components b1 and b2 in the composition.

[0093] Samples for mechanical testing

[0094] The samples were obtained according to ISO 1873-2:2007.

[0095] Charpy impact test determined according to ISO 179-1eA and ISO 1873-2.

[0096] Elongation at Yield: Measured according to ISO 527.

[0097] Elongation at break: measured according to ISO 527

[0098] Breaking stress: measured according to ISO 527.

[0099] Tensile Modulus: Measured according to ISO 527-2.

[0100] Melting point and crystallization point

[0101] The DSC was carried out under an inert N atmosphere at a scan rate of 20 °C / min with both cooling and heating. 2The melting point was measured on samples weighing between 5 mg and 7 mg at 400 °C. The instrument was calibrated with indium.

[0102] Determination of PP content in r-PE

[0103] 13 C NMR spectra were acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe operating at 120 °C in Fourier transform mode at 160.91 MHz.

[0104] CH 2 The peak of ethylene was used as an internal standard at 29.9 ppm. The samples were dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / vol% at 120 °C. Each spectrum was acquired with 90° pulses with a 15 s delay between pulses and CPD was used to remove 1 H- 13 C coupling. 512 transient data were stored in 32K data points using a spectral window of 9000 Hz.

[0105] The molar composition was obtained using the peak areas as follows (Table 1):

[0106] P=100A 3 / S

[0107] E=1000.5A 2 / S

[0108] Where S = 0.5A 2 +A 3

[0109] The molar contents were converted to weights using the monomer molecular weights.

[0110] Table A: Distribution of PP / PE blends

[0111]

[0112]

[0113] Examples

[0114] Example 1

[0115] In a plant operating continuously according to the hybrid liquid-gas polymerization technology, operation was carried out under the conditions specified in Table 1.

[0116] The polymerization is carried out in the presence of the catalyst system in a series of two reactors equipped with means for transferring the product from one reactor to the reactor immediately adjacent thereto.

[0117] Preparation of solid catalyst components

[0118] At 0 °C, 250 ml of TiCl 4 While stirring, add 10.0 g of microspherical MgCl 2 1.9C 2 H 5 OH (prepared according to the method described in Example 2 of USP 4,399,054, but operated at 3000 rpm instead of 10000 rpm) and 9.1 mmol of diethyl 2,3-(diisopropyl)succinate. The temperature was raised to 100°C and maintained for 120 minutes. Then the stirring was stopped, the solid product was allowed to settle and the supernatant was siphoned off. Then 250 ml of fresh TiCl 4 The mixture was reacted at 120°C for 60 minutes and the supernatant was siphoned off. The solid was washed six times with anhydrous hexane (6 x 100 ml) at 60°C.

[0119] Catalyst system and prepolymerization treatment

[0120] The solid catalyst component described above was contacted with triethylaluminum (TEAL) and dicyclopentyldimethoxysilane (DCPMS) as external electron donor component for 24 minutes at 12° C. The weight ratios between TEAL and the solid catalyst component and between TEAL and DCPMS are specified in Table 1.

[0121] The catalyst system was then subjected to prepolymerization by maintaining it in suspension in liquid propylene at 20° C. for about 5 minutes before being introduced into the first polymerization reactor.

[0122] Polymeric components a) and b)

[0123] The polymerization operation is carried out continuously in a series of two reactors, and these reactors are equipped with the equipment that product is transferred from one reactor to the reactor next to it. As described in European Patent EP 782587, the first reactor is a gas phase polymerization reactor with two interconnected polymerization zones (riser and downcomer). The second reactor is a fluidized bed gas phase reactor. Respectively, polymer (a) is prepared in the first reactor, and polymer (b) is prepared in the second reactor. Temperature and pressure are maintained constant during the whole reaction. Hydrogen is used as a molecular weight regulator.

[0124] The gas phase (propylene, ethylene and hydrogen) was analyzed continuously via gas chromatography.

[0125] At the end of the run, the powder was discharged and dried under a stream of nitrogen. The polymerization parameters are reported in Table 1

[0126] Table 1 - Polymerization process

[0127]

[0128]

[0129] The polymer pellets of the heterophasic composition of Example 1 and Comparative Example 2 were then introduced into a twin screw extruder (Werner type extruder) where they were mixed with 10 wt% and 15 wt% (based on the total amount of polyolefin) of QCP5603 Ivory (r-PE commercialized by Lyondellbasell, which contains 10 wt% PP content) and a standard stabilizer package. The polymer pellets were extruded in a twin screw extruder at a rotation speed of 250 rpm and a melt temperature of 200° C. to 250° C. under a nitrogen atmosphere.

[0130] Table 2 - Characterization

[0131]

[0132]

[0133] The properties of the final compositions are reported in Table 3.

[0134] Table 3 - Properties of the final composition

[0135]

[0136] The above data indicate that the polymer composition according to the present disclosure shows better impact properties relative to the comparative example.

Claims

1. A polypropylene composition comprising: (a) from 45.7 wt% to 69.7 wt% of a crystalline propylene polymer having a 13 C-MNR measured on the fraction insoluble in xylene at 25° C., an amount of isotactic pentads (mmmm) higher than 97.0 mol % and a polydispersity index ranging from 3 to 15; (b) from 5.3 to 29.3 weight percent of an elastomeric copolymer of ethylene and propylene, said copolymer having a 13 The C-MNR measurement ranges from 30.0 wt% to 70 wt% of the repeating units derived from ethylene; Wherein in the blend of components a) and b): i) the xylene-soluble polymer fraction of components a) + b) at 25° C. ranges from 10.0 wt. % to 32.5 wt. %; ii) said polymer fraction of components a) + b) soluble in xylene at 25°C has an intrinsic viscosity value measured in tetralin at 135°C ranging from 1.5 dl / g to 2.8 dl / g; iii) By 13 The content of ethylene-derived units in said fraction soluble in xylene at 25° C., as measured by C-MNR, ranges from 24.4% to 43.5% by weight; iv) a melting point ranging from 148.0°C to 168.0°C as measured by DSC; v) melt flow rate (ISO 1133-1230°C / 2.16kg) ranging from 10.0 g / 10 min to 30.0 g / 10 min; The polypropylene composition further comprises: (c) from 3.0 wt% to 27.0 wt% recycled polyethylene (r-PE) having a melt flow rate (ISO 1133-1190°C / 2.16 Kg) from 0.1 g / 10 min to 10 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component; d) from 1.0 wt% to 15.0 wt% of a crystalline propylene homopolymer having a melt flow rate (ISO 1133-1230°C / 2.16kg) in the range of from 0.3 g / 10 min to 10.0 g / 10 min; and a 3 Up to 0.950g / cm 3 Density (ISO 1183-1); The entire composition has a melt flow rate (ISO 1133-1230°C / 2.16kg) value ranging from 3.0 g / 10 min to 21.0 g / 10 min; The percentages of (a), (b), (c) and (d) are relative to the sum of (a), (b), (c) and (d).

2. The polypropylene composition according to claim 1, wherein: Component (a) ranges from 47.7 wt % to 67.7 wt %; Component (b) ranges from 7.3 wt % to 27.3 wt %; Component (c) ranges from 5.0 wt % to 25.0 wt %; Component (d) ranges from 5.0 wt% to 13.0 wt%.

3. The polypropylene composition according to claim 2, wherein the polymer fraction of component a) + b) soluble in xylene at 25°C ranges from 14.0 wt% to 28.2 wt%.

4. The polypropylene composition according to any one of claims 1 to 3, having a melt flow rate (ISO 1133 - 1230°C / 2.16kg) ranging from 4.3 g / 10 min to 18.0 g / 10 min.

5. The polypropylene composition according to any one of claims 1 to 4, wherein component (c) has a PP content in an amount ranging from 5 to 10 wt.-%, based on the total amount of component (c).

6. The polypropylene composition according to any one of claims 1 to 5, wherein component (c) has a molecular weight ranging from 0.940 g / cm 3 Up to 0.965g / cm 3 The density (ISO 1183-1) and the melt flow rate (ISO 1133-1190°C / 2.16Kg ISO 1133-1) of from 0.1 g / 10 min to 1.0 g / 10 min.

7. The polypropylene composition according to any one of claims 1 to 6, wherein the polymer fraction of components a) + b) soluble in xylene at 25°C has an intrinsic viscosity value measured in tetralin at 135°C in the range from 1.7 to 2.7 dl / g.

8. The polypropylene composition according to any one of claims 1 to 7, wherein 13 The content of said ethylene-derived units in said fraction of components a) + b) soluble in xylene at 25°C as measured by C-MNR ranges from 31.0 wt% to 42.0 wt%.

9. The polypropylene composition according to any one of claims 1 to 8, wherein component (b) has 13 The C-MNR measurement ranges from 35.0 wt% to 60.0 wt% ethylene.

10. The polypropylene composition according to any one of claims 1 to 9, wherein the intrinsic viscosity of the xylene soluble fraction at 25°C of component a) + b) measured in tetralin at 135°C ranges from 1.7 to 2.7 dl / g.

11. The polypropylene composition according to any one of claims 1 to 10, wherein the melting point of components a) + b measured by DSC ranges from 154.0 to 167.0°C.

12. The polypropylene composition according to any one of claims 1 to 11, wherein component d) has a melt flow rate (ISO 1133 - 1230°C / 2.16kg) ranging from 1.0 g / 10 min to 5.0 g / 10 min.

13. The polypropylene composition according to any one of claims 1 to 12, wherein component d) has a g / cm 3 Up to 0.930g / cm 3 Density (ISO 1183-1).

14. An injection molded article made from the composition according to claims 1 to 13.

15. The injection molded article according to claim 14, which has the form of an automobile battery box.

Citation Information

Patent Citations

  • Components and catalysts for the polymerization of olefins

    EP0045977A2

  • Process and apparatus for the gas-phase polymerization of alpha-olefins

    EP0782587A1

  • Process and apparatus for the gas-phase polymerisation

    EP1012195A1

  • Components and catalysts for the polymerization of olefins

    US4522930A

  • Components and catalysts for the polymerization of olefins

    WO2000063261A1